2017
DOI: 10.1371/journal.pone.0173784
|View full text |Cite
|
Sign up to set email alerts
|

Common and rare exonic MUC5B variants associated with type 2 diabetes in Han Chinese

Abstract: Genome-wide association studies have identified over one hundred common genetic risk variants associated with type 2 diabetes (T2D). However, most of the heritability of T2D has not been accounted for. In this study, we investigated the contribution of rare and common variants to T2D susceptibility by analyzing exome array data in 1,908 Han Chinese genotyped with Affymetrix Axiom® Exome Genotyping Arrays. Based on the joint common and rare variants analysis of 57,704 autosomal SNPs within 12,244 genes using Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, the effects of this SNP on the expression of MUC5B in ATII cells is unclear. The previous study showed that the expression of MUC5B was significantly elevated in pancreatic tissue of patients with T2DM compared to those without T2DM ( 38 ), therefore, we speculated that MUC5B rs2943512 (A>C) might cause the over-expression of MUC5B in lung tissue of T2DM patients. Even beyond the potential influence of the genetic factor of MUC5B SNP rs2943512, whether high glucose itself could cause the over-expression of MUC5B to mediate ATII cells injury and thus trigger pulmonary fibrosis is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…However, the effects of this SNP on the expression of MUC5B in ATII cells is unclear. The previous study showed that the expression of MUC5B was significantly elevated in pancreatic tissue of patients with T2DM compared to those without T2DM ( 38 ), therefore, we speculated that MUC5B rs2943512 (A>C) might cause the over-expression of MUC5B in lung tissue of T2DM patients. Even beyond the potential influence of the genetic factor of MUC5B SNP rs2943512, whether high glucose itself could cause the over-expression of MUC5B to mediate ATII cells injury and thus trigger pulmonary fibrosis is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…We conducted an African ancestry T2D meta-analysis that included this GWAS and an African American meta GWAS 7 consisting of five studies ( n = 8599); the Atherosclerosis Risk in Communities (ARIC), the Cleveland Family Study (CFS), the Howard University Family Study (HUFS), Jackson Heart Study (JHS), and Multi-Ethnic Study of Atherosclerosis (MESA). This African ancestry meta-analysis revealed four genome-wide significant loci (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Individual-level genotype and phenotype data were obtained by authorized access to dbGaP. The China America Diabetes Mellitus (CADM) study is a case-control study of T2D in China [17]. The Africa America Diabetes Mellitus (AADM) study is a case-control study of type 2 diabetes in Africans [18,19].…”
Section: Replication Analysismentioning
confidence: 99%